The relationship between politics and music of the black community - Tomaszewicz, Sara Anastazja (Journal of Education, Health and Sport, 2017)
Article demonstrate the complex relationships between politics and music. It show what is the role of music in political life. In the article we find out why the musical genre of rap is seen as a form of hostility, who is the representative of this music and what prompted artists to engage in this music. We'll find out whether the artist can influence through his work on society and whether it can persuade listeners to the revolution.